BRINGING DEBATE INTO CLASSROOM: THE PERSPECTIVE OF EFL TEACHERS IN ACEH - Mulyadi Syahputra; Rosdiana Rosdiana; Zahria Amalina; Said Miftahul Fahmi; Wahidah Nasution (JURNAL EDUSCIENCE, 2025)
Purpose - This study aims to explore the perceptions of English as a Foreign Language (EFL) teachers regarding the use of parliamentary debate as a classroom instruction in Aceh, a Sharia-governed province in Indonesia. It investigates whether the assumption of Islamic-based education restricts the use of debate as a tool to enhance critical thinking. This investigation aimed to fill the research gaps where exploration had not been conducted yet.Methodology - A quantitative descriptive survey design was employed to collect data from 252 EFL teachers across general and Islamic secondary schools in Aceh. A structured, closed-ended questionnaire (using a Likert scale) was administered, selected through stratified random sampling based on specific criteria. The instrument was developed to assess three matrices they are (1) the understanding, (2) acceptance, and (3) evaluation. The data was then analyzed for Mean and Standard Deviation.Findings - The findings indicated a positive attitude toward integrating debate into classroom teaching tools for either critical thinking or language proficiency development. However, aligning the debate topics with Aceh's socio-religious norms is necessary to avoid overly liberal or sensitive issues that may be perceived as offensive. Although there is a strong acceptance of debate in the classroom and an understanding of the debate's nature, the teachers' procedural understanding of the debate remains lacking.Contribution - These findings suggest that the adoption of parliamentary debate in Aceh's EFL classrooms necessitates adjustments, indicating that Western teaching models, such as debate, must be localized within Islamic educational frameworks.